MANAJEMEN IMPLEMENTASI KURIKULUM MERDEKA DALAM PENDIDIKAN ISLAM: INTEGRASI PROFIL PELAJAR PANCASILA DAN NILAI KEISLAMAN - Mahdalena; Adinda Syah Nabila; Mahyiddin; M. Fadli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the Independent Curriculum is an educational transformation effort oriented towards the holistic development of students' competencies, character, and potential. In the context of Islamic education, curriculum implementation focuses not only on achieving the Pancasila Student Profile but also on strengthening Islamic values ​​that serve as the foundation for student character formation. This study aims to analyze the management of the Independent Curriculum implementation in Islamic education through the integration of the Pancasila Student Profile dimensions with Islamic values. The study used a qualitative approach with library research methods sourced from various scientific literature, educational policies, and studies related to the Independent Curriculum and Islamic education. The results show that the successful implementation of the Independent Curriculum in Islamic education is determined by management functions that include systematic planning, organizing, implementing, and evaluating. The integration of the Pancasila Student Profile with Islamic values ​​can be realized through curriculum development, project-based learning, school culture familiarization, and educator role models. The dimensions of faith, devotion to God Almighty, and noble character serve as a meeting point that strengthens religious values, while other dimensions, such as mutual cooperation, critical thinking, creativity, independence, and global diversity, align with the principles of Islamic teachings. Thus, the integrated management of the Independent Curriculum implementation with Islamic values ​​contributes to developing students with character, competence, and adaptability, with a strong Islamic identity to face the challenges of the 21st century.